Developing digital learning materials using whiteboard animation for middle and high schools - Wahyu Taufiq; Dian Rahma Santoso; Joko Susilo (Universitas Muhammadiyah Magelang, 2022)
Educators are encouraged to develop their technology integration abilities as information and communication technology (ICT) advances in the field of education. This has ramifications for school curriculum, which must be able to adapt to changing circumstances in order to satisfy the educational demands of pupils during the industrial revolution. 4.0. Training on the construction of digital learning materials utilizing whiteboard animation is one of the initiatives to overcome the aforementioned difficulties. After 50 hours of training, the teachers at 'Aisyiyah Middle and Hight Schools (SMP and SMA) in the Lawang sub-district were able to generate instructional materials by constructing material situations, which were then translated into Whiteboard animation. The teachers noted that understanding the chosen application was tough at first, but with effort and the help of the training materials, everyone was able to make their first whiteboard animation. The vast majority of participants want to use this program to create further materials. It is also hoped that in the future, similar materials or their development will be available.